The aspirations and realities of prison education for under-25s in the London area (UCL Press, 2014)
The purpose of this study, undertaken in 2012, was to describe provision available for under25s in prisons and to gain insight into the particularities of prison education. Six custodial establishments serving the London area were visited (prisons or Young Offender Institutions) and available statistical data were collected from a larger sample. Main findings were that, whilst many prisons are working hard to offer good provision, prison education is constrained in terms of the options available, and the length and level of courses. Some useful methods for addressing some of these problems were being used in different contexts. However, in conclusion, prisons need to focus more on education, training, and employment if they are to provide viable support for young prisoners as they move back into society. The proportion of education and training options at or above Level 2 should be increased.